Effect of ozone gas on cultures of Candida albicans and Aspergillus fumigatus: evaluation of two ozonation devices - Maicon Henrique Caetano; Adriano Menis Ferreira; Denise de Andrade; Álvaro Francisco Lopes de Sousa; Liliane Moretti Carneiro; Alessandra Lyrio Barbosa; Herica Emilia Félix de Carvalho; Marcelo Alessandro Rigotti; Margarete Teresa Gottardo de Almeida (Journal of Infection in Developing Countries)
Introduction: Candida albicans and Aspergillus fumigatus are two important agents of Healthcare-associated infections. This study aimed to evaluate the antifungal activity of ozone (O3) gas produced by two commercial devices against cultures of these two species.